Monogenic Epilepsies: Channelopathies, Synaptopathies, mTorpathies, and Otheropathies - Praticò, Andrea D.; Falsaperla, Raffaele; Polizzi, Agata; Ruggieri, Martino (Journal of Pediatric Neurology, 2021)
Epilepsy has been historically defined as the recurrence of two or more seizures, together with typical electroencephalogram (EEG) changes, and significant comorbidities, including cardiac and autonomic changes, injuries, intellectual disability, permanent brain damage, and higher mortality risk. Epilepsy may be the consequence of several causes, including genetic anomalies, structural brain malformations, hypoxic–ischemic encephalopathy, brain tumors, drugs, and all contributing factors to the imbalance between excitatory and inhibitory neurons and modulatory interneurons which in turn provoke abnormal, simultaneous electric discharge(s) involving part, or all the brain. In the pregenetic, pregenomic era, in most cases, the exact cause of such neuronal/interneuronal disequilibrium remained unknown and the term “idiopathic epilepsy” was used to define all the epilepsies without cause. At the same time, some specific epileptic syndromes were indicated by the eponym of the first physician who originally described the condition (e.g., the West syndrome, Dravet syndrome, Ohtahara syndrome, and Lennox–Gastaut syndrome) or by some characteristic clinical features (e.g., nocturnal frontal lobe epilepsy, absence epilepsy, and epilepsy and mental retardation limited to females). In many of these occurrences, the distinct epileptic syndrome was defined mainly by its most relevant clinical feature (e.g., seizure semiology), associated comorbidities, and EEGs patterns. Since the identification of the first epilepsy-associated gene (i.e., CHRNA4 gene: cholinergic receptor neuronal nicotinic α polypeptide 4), one of the genes responsible for autosomal dominant nocturnal frontal lobe epilepsy (currently known as sleep-related hypermotor epilepsy) in 1995, the field of epilepsy and the history of epilepsy gene discoveries have gone through at least three different stages as follows: (1) an early stage of relentless gene discovery in monogenic familial epilepsy syndromes; (2) a relatively quiescent and disappointing period characterized by largely negative genome-wide association candidate gene studies; and (3) a genome-wide era in which large-scale molecular genetic studies have led to the identification of several novel epilepsy genes, especially in sporadic forms of epilepsy. As of 2021, more than 150 epilepsy-associated genes or loci are listed in the Online Mendelian Inheritance in Man database.
Keywords: epilepsy; genetics; monogenic; ion channels; synapsis proteins; mTOR; protein